2018
DOI: 10.1002/anie.201806763
|View full text |Cite
|
Sign up to set email alerts
|

Ring Opening Metathesis Polymerization of Bicyclic α,β‐Unsaturated Anhydrides for Ready‐to‐be‐grafted Polymers Having Tailored pH‐Responsive Degradability

Abstract: Polymers having α,β-unsaturated anhydrides as repeating units were synthesized by ring opening metathesis polymerization (ROMP). The anhydride moieties were ready-to-be-grafted with amines to form acid-labile cis-α,β-unsaturated acid amide linkages. The pH-responsive reversible de-grafting can be controlled by changing the intramolecular accessibility between acid and amide groups. The alendronate-grafted ROMP polymers showed distinct pH-dependent cytotoxicity according to the anhydride structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The β-carboxylic acid amides containing cis -α,β-double bond can be degraded into corresponding amine derivatives and anhydrides/dicarboxylic acids under weakly acidic conditions. 29 More interestingly, it was found that their pH sensitivity can be tuned by altering the substituents on the cis -double bond, 20 and the di-substituted maleic acid amide (1-methyl-2-(2′-carboxyethyl) maleic acid amide, DMAA) derivatives are reported to undergo hydrolysis at pH < 6.8. 21 DMA was thus chosen as the linker for AIEgen–antibody conjugation.…”
Section: Resultsmentioning
confidence: 99%
“…The β-carboxylic acid amides containing cis -α,β-double bond can be degraded into corresponding amine derivatives and anhydrides/dicarboxylic acids under weakly acidic conditions. 29 More interestingly, it was found that their pH sensitivity can be tuned by altering the substituents on the cis -double bond, 20 and the di-substituted maleic acid amide (1-methyl-2-(2′-carboxyethyl) maleic acid amide, DMAA) derivatives are reported to undergo hydrolysis at pH < 6.8. 21 DMA was thus chosen as the linker for AIEgen–antibody conjugation.…”
Section: Resultsmentioning
confidence: 99%
“…114,115 One typical example is β-carboxylic amide bonds. 116 Liu et al prepared a nanomaterial that achieved a charge shift from negative to positive in response to the tumor micro-acidic environment for the treatment of glioma. They developed a nanoparticle with a three-layer core–shell structure: from inside to outside, an inner polyethyleneimine (PEI) siRNA complex, a negatively charged citric anhydride grafted poly(lysine) (PLL-CA) layer in the middle, and an outer angiopep-2 modified hemoglobin membrane.…”
Section: Stimulus-responsive Nanoparticles With Transformable Physico...mentioning
confidence: 99%
“…The anhydride obtained with cyclopentadiene can undergo ethylene extrusion at 110 °C by Alder-Rickert reaction . Polymers from bicyclic α,β-unsaturated anhydrides could be obtained by ring-opening metathesis polymerization (ROMP), and the furan ring could be cleaved by FeCl 3 , as it has an allyl ether structure …”
Section: Part 2 – the Use Of Cyclic Anhydrides In Bioconjugate Chemistrymentioning
confidence: 99%
“…131 Polymers from bicyclic α,β-unsaturated anhydrides could be obtained by ring-opening metathesis polymerization (ROMP), and the furan ring could be cleaved by FeCl 3 , as it has an allyl ether structure. 132 14. 1,2-cis-Cyclohexanedicarboxylic Anhydride (3,4,5,6-Tetrahydrophthalic Anhydride, THPA).…”
Section: ■ Introductionmentioning
confidence: 99%